Zinc asparaginate supplementation induces redistribution of toxic trace elements in rat tissues and organs - Skalny, Andrey A. (Interdiscip Toxicol, 2015)
The primary objective of the current study was the investigation of the influence of zinc asparaginate supplementation for 7 and 14 days on toxic metal and metalloid content in rat organs and tissues. Rats obtained zinc asparaginate in doses of 5 and 15 mg/kg/day for 7 and 14 days. At the end of the experiment rat tissues and organs (liver, kidney, heart, m. gastrocnemius, serum, and hair) were collected for subsequent analysis. Estimation of Zn, Al, As, Li, Ni, Sn, Sr content in the harvested organs was performed using inductively coupled plasma mass spectrometry at NexION 300D. The obtained data showed that intragastric administration of zinc significantly increased liver, kidney and serum zinc concentrations. Seven-day zinc treatment significantly affected the toxic trace element content in the animals’ organs. Zinc supplementation significantly decreased particularly liver aluminium, nickel, and tin content, whereas lead tended to increase. Zinc-induced changes in kidney metal content were characterized by elevated lithium and decreased nickel concentration. Zinc-induced alteration of myocardical toxic element content was multidirectional. Muscle aluminium and lead concentration were reduced in response to zinc supplementation. At the same time, serum and hair toxic element concentrations remained relatively stable after 7-day zinc treatment. Zinc asparaginate treatment of 14 days significantly depressed liver and elevated kidney lithium content, whereas a significant zinc-associated decrease was detected in kidney strontium content. Zinc supplementation for 14 days resulted also in multidirectional changes in the content of heart toxic elements. At the same time, significant zinc-associated decrease in muscle lithium and nickel levels was observed. Fourteen-day zinc treatment resulted in significantly increased serum arsenic and tin concentrations, whereas hair trace element content remained relatively stable. Generally, the obtained data indicate a significant redistribution of toxic metals in the animal organism under zinc supplementation.